Data Security and Privacy in the Digital Era: Challenges for Modern Government - Sarjito, Aris (Universitas Bojonegoro, 2024)
In the digital age, data security and privacy are paramount for modern governments, which are facing increasing cyber threats that impact operations and public trust. This research aims to explore the challenges and strategies in managing data security and privacy, focusing on three key areas: the impact of cyberattacks on governmental operations and public trust, the effectiveness of current data protection regulations and cybersecurity measures, and balancing transparency with data security in open data initiatives. Using qualitative research methods and secondary data analysis, the study examines recent high-profile incidents, such as the SolarWinds hack, and evaluates regulatory frameworks such as the GDPR. The findings highlight that cyberattacks disrupt government functions and undermine public trust, while compliance and enforcement challenges undermine the efficacy of data protection measures. Furthermore, successful strategies for balancing transparency and data security include robust anonymization techniques and stringent access controls. The study concludes that continuous evaluation and adaptation of data security policies are essential for mitigating risks and restoring public confidence. Keywords: cyberattacks; data security; open data initiatives; public trust